Architecture of lacustrine mass-transport complexes in the Mesozoic Songliao Basin, China. (December 2016) - Zhang, Chenchen; Wei, Wei; Zhang, Shun; Wu, Chaodong; Fu, Xiuli; Cui, Kunning
Abstract: 3-D seismic data and wireline log profiles of the Central Depression in the Songliao Basin exhibit four lacustrine mass-transport complexes (MTCs) in the second and the third members of the Upper Cretaceous Nenjiang Formation. The mass-transport complex named MTC-A lies in the north of the Daqing Anticline with an area of approximately 95 km 2 and a maximum thickness of 62 m. It consists of five laterally and vertically stacked blocks striking E-W and has a convex-downslope front. The mass-transport complex named MTC-C is located in the south of the Daqing Anticline consisting of seven blocks. This MTC strikes NNE-SSW and has an area of approximately 61.5 km 2 and a maximum thickness of 55 m. MTC-B, the mass-transport complex lying in the middle of the Daqing Anticline, consists of three vertically stacked blocks and has a semi-circular outline striking E-W. MTC-B has an area of approximately 24 km 2 and a maximum thickness of 92 m. Along the Daqing Anticline from north to south, the three MTCs distribute in lacustrine facies in the NNE direction. The mass-transport complex named MTC-D located in the southeast of the Daqing Anticline has an area of approximately 150 km 2 with a maximum thickness of 135 m striking E-W, which is rich in mudstones. MTC-D is characterized by the three-layer architecture vertically consisting of a dragged layer at the bottom, a slumped layer in the middle, and a stable layer at the top. Besides, in the plane view, MTC-D can be divided into three parts according to the sliding distance and stacking pattern of the slip blocks: the detaching area, the stacking area and the drifting area. The MTCs are characterized by thickening upslope and thin-out downslope. Siltstones and very fine sandstones occur in 2–4 beds that are cumulatively 0.8–7 m thick in the upslope and central parts of the MTCs. The edges of the blocks are composed of mudstone. Seismic amplitude slices reveal arcuate or straight ridges on the block surfaces with a spacing density of 4–10 per kilometer and a height ranging from 25 to 40 m. The arcuate ridge paleo-morphology on the MTC surfaces suggests that blocks are slump bodies. The estimated minimum water depth at the time of the MTC emplacement is 30–70 m, and the sliding distance is 2–10 km. From 3-D seismic amplitude slices, no feeding channel connected to the mass-transport complexes is found. Besides, coupled with the continuous ridges on blocks and the clear and flat lateral edges suggest that mass-transport complexes belong to the prodelta slump bodies. Thus, the triggering mechanism of the MTCs may be closely related to earthquakes caused by volcanic activities with the evidence of three cinerite layers shown in the well cores. Highlights: We exhibit four mass-transport complexes in lacustrine facies of continental basin. We depict a three-layer structure of dragged layer, slumped layer and stable layer. The MTCs are most likely to be triggered by earthquake caused by volcanic activity. The sandstones in the MTCs are favourable to form accumulation and lithologic trap.